Liver Histological Response of Female Broodstock Catfish to Dietary Soybean Meal Supplementation - VIKA MAULIDIYAH; Rizky Kusma Pratiwi; Muhamad Dwi Cahya; Zakiyyah Nur Inayah; Vina Nur Nadiro; Anissa Aprilia Nurkhasanah; Maura Yasmin Dhia; Fajar Maulana Akmal Firdaus (Universitas Nusa Bangsa, 2026)
Feed is one of the key factors in fish culture, including the use of plant-based ingredients such as soybean meal as an alternative protein source that may affect the physiological condition of organs, particularly the liver. This study aimed to analyse the effect of soybean meal supplementation in feed on the liver histological response of catfish (Clarias sp.). Liver histological characteristics were evaluated in three treatment groups: a control group (without soybean meal supplementation), 5% soybean meal-supplemented diet, and 10% soybean meal-supplemented diet. The results showed that the control group exhibited a relatively normal liver histological structure, characterised by an orderly arrangement of hepatocytes, centrally located nuclei, and clearly visible sinusoids. In the 5% soybean meal treatment, more pronounced histological alterations were observed, particularly cytoplasmic vacuolization of hepatocytes, indicating moderate to severe steatosis. Meanwhile, hepatocyte vacuolization was also observed in the 10% soybean meal treatment, but with a severity ranging from mild to moderate compared with the 5% treatment. These findings indicate that dietary soybean meal supplementation affects liver histology in catfish through a non-linear response pattern. The 5% dose caused greater tissue alterations than the 10% dose, which may be associated with the adaptive response of hepatocytes to feed exposure. These findings indicate that the use of soybean meal in fish feed should consider an appropriate dosage to maintain liver health.